Religious Practices and Its Impacts on a Sustainable Urban Environment in Nigeria: The Way Forward - Timothy Oyebamiji Ogunbode; Funke Elizabeth Oyekan (The Scientific World Journal)
A sustainable and serene environment is a prerequisite and a driver of human productivity in space and time. The quality of a human environment, however, is under threat always partly as a result of various human cultural activities such as festivities and religious practices. This work specifically investigated various ways religious activities have impacted the urban environment in two cities in the southwestern part of Nigeria together as a case study. Data for the work were generated through the administration of 250 copies of the structured questionnaire, out of which 232 were completed and retrieved. The data were subjected to data adequacy tests (i.e., Kaiser–Meyer–Olkin (KMO) and Bartlett’s test of sphericity (BTS)). The test showed 67.6% at a significance level of p < 0.001 The results showed that 52.6% were of secondary school level, 52.2 were of Christian faith, and 61.6% were also of the male gender who were mostly in the age category of 46 to 65 years. The factor analysis identified 11 out of 23 variables as significant ones which explained 72.052% of the ways religious activities have negatively impacted the urban environment. Of the 11 variables, the first six alone offered 45.248%, namely, (i) contribution to climate change, (ii) night worships, (iii) noise pollution caused, (iv) use of the public address system, (v) quest for expansion, and (vi) religious uses of natural resources, especially water. In view of this, it is recommended that efforts should be made to check the extracted variables for a sustainable serene environment. However, there is a need to put in place relevant legislation/policies to control the activities of various religious bodies and mechanisms to enlighten religious practitioners on practices that will not jeopardize a serene urban environment. Further studies in other places to affirm or otherwise the findings here are suggested.